Preparation of Glutathione-Responsive Paclitaxel Prodrug Based on Endogenous Molecule of L-Glutathione Oxidized for Cancer Therapy - Xiao Duan; Qiang Wang; Yue Wang; Xinping Liu; Manman Lu; Zhifang Li; Xuelian Jiang; Jingquan Ji (MDPI AG, 2024)
Using an endogenous carrier is the best method to address the biocompatibility of carriers in the drug delivery field. Herein, we prepared a glutathione-responsive paclitaxel prodrug micelle based on an endogenous molecule of L-glutathione oxidized (GSSG) for cancer therapy using one-pot synthesis. The carboxyl groups in L-glutathione oxidized were reacted with the hydroxyl group in paclitaxel (PTX) using the catalysts dicyclohexylcarbodiimide (DCC) and 4-dimethylaminopyridine (DMAP). Then, the amino-polyethylene glycol monomethyl ether (mPEG-NH2) was conjugated with GSSG to prepare PTX-GSSG-PEG. The structure of PTX-GSSG-PEG was characterized using infrared spectroscopy (FT-IR), nuclear magnetic resonance spectroscopy (NMR), and mass spectrometry (MS). The drug release kinetics of PTX within PTX-GSSG-PEG were quantified using ultraviolet spectroscopy (UV-Vis). The size of the PTX-GSSG-PEG micelles was 83 nm, as evaluated using dynamic light scattering (DLS), and their particle size remained stable in a pH 7.4 PBS for 7 days. Moreover, the micelles could responsively degrade and release PTX in a reduced glutathione environment. The drug loading of PTX in PTX-GSSG-PEG was 13%, as determined using NMR. Furthermore, the cumulative drug release rate of PTX from the micelles reached 72.1% in a reduced glutathione environment of 5 mg/mL at 120 h. Cell viability experiments demonstrated that the PTX-GSSG-PEG micelles could induce the apoptosis of MCF-7 cells. Additionally, cell uptake showed that the micelles could distribute to the cell nuclei within 7 h. To sum up, with this glutathione-responsive paclitaxel prodrug micelle based on the endogenous molecule GSSG, it may be possible to develop novel nanomedicines in the future.